Associations of pain sensitisation with tender and painful joint counts in people with hand osteoarthritis: results from the Nor-Hand study. Issue 1 (5th January 2022) - Gløersen, Marthe; Steen Pettersen, Pernille; Neogi, Tuhina; Slatkowsky-Christensen, Barbara; Kvien, Tore K; Magnusson, Karin; Hammer, Hilde Berner; Haugen, Ida K
Abstract : Objective: To examine associations of pain sensitisation with tender and painful joint counts and presence of widespread pain in people with hand osteoarthritis (OA). Methods: Pressure pain thresholds (PPT) at a painful finger joint and the tibialis anterior muscle, and temporal summation (TS) were measured in 291 persons with hand OA. We examined whether sex-standardised PPT and TS values were associated with assessor-reported tender hand joint count, self-reported painful hand and total body joint counts and presence of widespread pain using linear and logistic regression analyses adjusted for age, sex, body mass index, education and OA severity. Results: People with lower PPTs at the painful finger joint (measure of peripheral and/or central sensitisation) had more tender and painful hand joints than people with higher PPTs. PPT at tibialis anterior (measure of central sensitisation) was associated with painful total body joint count (beta=−0.82, 95% CI −1.28 to –0.35) and presence of widespread pain (OR=0.57, 95% CI 0.43 to 0.77). The associations between TS (measure of central sensitisation) and joint counts in the hands and the total body were statistically non-significant. Conclusion: This cross-sectional study suggested that pain sensitisation (ie, lower PPTs) was associated with joint counts and widespread pain in hand OA. This knowledge may be used for improved pain phenotyping of people with hand OA, which may contribute to better pain management through more personalised medicine. Further studies are needed to assess whether a reduction of pain sensitisation leads to a decrease in tender and painful joint counts.